Danube Free Zones – between Desiderata and Achievements: Array - Puscaciu, Rose-Marie; Puscaciu, Viorica (Journal of Danubian Studies and Research, 2020)
The notion of free zone, appears frequently in commercial discussions, as being the place where you can develop a business, due to several facilities offered to both importers and exporters - facilities of a customs, fiscal and commercial nature. Many companies use the advantages of the free zone regime, as a good tool for fiscal optimization of costs. Under the conditions of globalization, it is becoming increasingly important to use tools that optimize the flow of goods. In this sense, free zones are the most suitable tools for optimizing both the flows of goods and the financial ones of companies. With so many advantages it presents a free area related to a waterway, such as the Danube River. Our study aims to analyze the opportunities and achievements of the free zones related to the Danube, in Romania; the addressability of this analysis is both to the business environment and to the academic one. The analysis methods are by excellence qualitative, thematic, comparative, applying the study, the expertise. Our study can be useful both to business people, as well as to researchers, students in the economic field; therefore, any suggestions for improvement will be welcome.